2018
DOI: 10.1111/jpn.12999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc oxide sources and dosages on gut microbiota and integrity of weaned piglets

Abstract: Zinc oxide (ZnO) supplied at pharmacological dosage in diets of weaned piglets improves growth performance. However, it causes environmental contamination and induces bacterial antibiotic resistance, yet this practice is debated. The effects on gut microbiota and integrity in weaned piglets of conventional ZnO at nutritional and pharmacological dosage (110 and 2,400 mg/kg Zn, respectively) were compared to an alternative ZnO source at 110 and 220 mg/kg Zn. Each of the four treatments was applied to four pens (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 46 publications
(70 reference statements)
3
47
0
Order By: Relevance
“…Various studies have reported that pharmacological dietary inclusions of ZnO modify the GIT microbial community, including reductions in diversity and evenness [ 16 ], anaerobes [ 17 ], Enterobacteriaceae [ 18 ], clostridia and coliforms [ 19 ], E. coli [ 20 ], lactic acid bacteria and lactobacilli [ 21 ], and/or increases in coliforms and enterococci [ 21 ] or lactobacilli [ 19 ], evidently with opposite or contradictory effects sometimes reported. More recently, Pieper et al [ 16 ] reported higher abundances of Bacteroides , Parabacteroides , Collinsella , Acetivibrio , Blautia , Coprococcus , Faecalibacterium , Subdoligranulum and lower abundances of Megasphaera , Dialister , Acidaminococcus , and Ruminococcus in the colon of weaned pigs fed 2500 mg/kg ZnO using metagenomic sequencing.…”
Section: Zinc Copper and Manganese Influences On Intestinal Healthmentioning
confidence: 99%
“…Various studies have reported that pharmacological dietary inclusions of ZnO modify the GIT microbial community, including reductions in diversity and evenness [ 16 ], anaerobes [ 17 ], Enterobacteriaceae [ 18 ], clostridia and coliforms [ 19 ], E. coli [ 20 ], lactic acid bacteria and lactobacilli [ 21 ], and/or increases in coliforms and enterococci [ 21 ] or lactobacilli [ 19 ], evidently with opposite or contradictory effects sometimes reported. More recently, Pieper et al [ 16 ] reported higher abundances of Bacteroides , Parabacteroides , Collinsella , Acetivibrio , Blautia , Coprococcus , Faecalibacterium , Subdoligranulum and lower abundances of Megasphaera , Dialister , Acidaminococcus , and Ruminococcus in the colon of weaned pigs fed 2500 mg/kg ZnO using metagenomic sequencing.…”
Section: Zinc Copper and Manganese Influences On Intestinal Healthmentioning
confidence: 99%
“…Collectively, ZnO is a powerful immunomodulatory nutrient for piglets, but its effectiveness seems to depend on the levels of ZnO. Zinc administration is known to induce changes in the gut microbiome; ZnO supplementation reduces the abundance of opportunistic pathogens including Campylobacterales, Enterobacteriaceae, and Escherichia, resulting in improved gut integrity [ 14 , 15 , 16 ]. Despite the recently demonstrated beneficial effects of ZnO usage, many efforts have been made to reduce its excessive use in piglets as high levels of ZnO in the diets of weaned pigs are mostly excreted, resulting in markedly high concentration of zinc in the soil [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…During past two decades, numerous studies have focused on the development of alternatives to antibiotics to maintain swine health and performance (Thacker, 2013; Wang J. et al, 2018). The most widely researched non-antibiotic alternatives include probiotics, prebiotics, acidifiers, and essential oils (Valeriano et al, 2016; Gresse et al, 2017; Wang W. et al, 2018). Among these alternatives, probiotics have higher potential to act as feed additives against pathogens (Gresse et al, 2017; Azad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%